Immunoradiometric Assays for Human Coagulation Factor VII Using Polyclonal Antibodies Against the Ca(II)-Dependent and Ca(II)-Independent Conformation - Bom, V J J; van Tilburg, N H; Es, C Krommenhoek-van; Bertina, R M (Thrombosis and Haemostasis, 1986)
Human coagulation factor VII is a trace plasma protein belonging to the vitamin K-dependent factors. Two specific and sensitive immunoradiometric assays for factor VII were developed using immunopurified rabbit antibodies against the Ca(II)-independent and Ca(II)-dependent conformation of factor VII. Both assays were insensitive to the activation state of factor VII. The distribution of factor VII antigen was studied in 40 healthy individuals and the antigen level in normal plasma was calculated to be 0.52-0.62 μg/ml. The two assays were used in a comparative study of factor VII procoagulant activity and factor VII antigen in patients treated with oral anticoagulants.
Keywords: Factor VII; Immunoradiometric assay; Calcium; Oral anticoagulation; Factor VII deficiency